Psychological capital mediates the mindfulness-creativity link: the perspective of positive psychology - He, Wu-jing (Frontiers in Psychology, 2024)
The positive mindfulness-creativity link has been widely documented; however, its underlying psychological mechanisms remain less understood. From the perspective of positive psychology, this study examined the mediating effect of psychological capital (PsyCap) on the effect of dispositional mindfulness on creative functioning. A total of 894 Chinese secondary school students in Hong Kong (50.8% female; Mage = 15.5 years) completed the study. A cross-sectional design was used, in which context PsyCap and dispositional mindfulness were assessed by the Chinese version of the revised Compound PsyCap Scale (CPC-12R) and the Mindful Attention Awareness Scale (MAAS), respectively. Moreover, by adopting the multiple-measurement approach to creativity, three commonly used creativity tests (i.e., the Wallach-Kogan Creativity Test/WKCT, the Test for Creative Thinking-Drawing Production/TCT-DP, and the Creative Problem-Solving Test/CPST) were applied to capture three aspects of creativity (i.e., divergent thinking, creative combination, and creative problem solving). The results suggest that (1) PsyCap partially but significantly mediated the mindfulness-creativity link for all three aspects of creative functioning, and (2) PsyCap demonstrated the strongest effect size in mediating the mindfulness-creativity link for creative problem solving, followed by creative combination and then divergent thinking. These results, on the one hand, support the positive psychology perspective by confirming a positive psychological resource mechanism regarding the relationship between mindfulness and creativity. On the other hand, the results regarding the varied sizes of the mediation effect further enrich the discourse on this perspective by showing that the mediation mechanism may function to different degrees depending on which aspect of creativity is under consideration. These findings illuminate the positive functioning of mindfulness, psychological resources/capital and creativity.